Assessing the causal associations of sleep apnea with mental health and socioeconomic status: a bidirectional two-sample Mendelian randomization - Yuan Wu; Zuming Li; Xueru Chen; Siyi Wu; Xuemei Zhong; Aifang Zheng; Li Li; Hai Chen; Jiqiang Li; Yue Lu; Jiankun Chen; Kao Gan (BMC, 2024)
Abstract Objective Traditional observational research has suggested a connection between socioeconomic position, mental health, and sleep apnea (SA), but the specifics of this connection are still unclear. Using the Mendelian randomization approach, we intended to evaluate the potential causal link between mental health, socioeconomic status, and SA. Methods Our research employed summary statistics data from large-scale genome-wide association studies (GWAS) on mental health, socioeconomic status, and SA. In the main study, the connection between mental health, socioeconomic status, and SA was examined using the inverse variance weighted approach. In addition, as a supplement, we also used other Mendelian randomization methods, including MR Egger, weighted median, simple mode, and weighted mode. Results The primary analysis showed that educational attainment, including longer years of schooling, college or university degree, and higher intelligence was associated with a lower risk of SA (OR = 0.750, 95%CI = 0.653-0.862; OR = 0.558, 95%CI = 0.423-0.735; OR = 0.871, 95%CI = 0.760-0.999, respectively), while social deprivation was associated with a higher risk of SA (OR = 1.821, 95%CI = 1.075-3.085). And the income was not associated with the risk of sleep apnea (OR = 0.877, 95%CI = 0.682-1.129). In mental health exposure, major depressive disorder was associated with a higher risk of sleep apnea (OR = 1.196, 95%CI = 1.015-1.409), while attention-deficit hyperactivity disorder, bipolar disorder, and schizophrenia were not associated with the risk of sleep apnea (OR = 1.064, 95%CI = 0.958-1.181; OR = 1.030, 95%CI = 0.942-1.127; OR = 0.990, 95%CI = 0.957-1.025, respectively). Reverse MR analysis failed to find a causal effect from SA on mental health and socioeconomic status. Conclusions This MR investigation offers proof of a possible causal relationship between SA, socioeconomic level, and mental health.